Anatomy of F1-ATPase powered rotation. - Martin, J; Ishmukhametov, R; Hornung, T; Ahmad, Z; Frasch, W (National Academy of Sciences, 2014)
F1-ATPase, the catalytic complex of the ATP synthase, is a molecular motor that can consume ATP to drive rotation of the γ-subunit inside the ring of three αβ-subunit heterodimers in 120° power strokes. To elucidate the mechanism of ATPase-powered rotation, we determined the angular velocity as a function of rotational position from single-molecule data collected at 200,000 frames per second with unprecedented signal-to-noise. Power stroke rotation is more complex than previously understood. This paper reports the unexpected discovery that a series of angular accelerations and decelerations occur during the power stroke. The decreases in angular velocity that occurred with the lower-affinity substrate ITP, which could not be explained by an increase in substrate-binding dwells, provides direct evidence that rotation depends on substrate binding affinity. The presence of elevated ADP concentrations not only increased dwells at 35° from the catalytic dwell consistent with competitive product inhibition but also decreased the angular velocity from 85° to 120°, indicating that ADP can remain bound to the catalytic site where product release occurs for the duration of the power stroke. The angular velocity profile also supports a model in which rotation is powered by Van der Waals repulsive forces during the final 85° of rotation, consistent with a transition from F1 structures 2HLD1 and 1H8E (Protein Data Bank).